Removal of bisphenol a by microalgae - Duangrat Inthorn (2018)
Eighteen strains of microalgae were tested for Bisphenol A (BPA) removal by growing them in the presence of 20 μM BPA in aqueous solution. In green algae, BPA removal by Chlorella vulgaris var. vulgaris, Chlamydomonas sp. and Scenedesmus acuminatus var. acuminatus was 87%, 81% and 81%, respectively. In cyanobacteria, BPA removal by Hapalosiphon hibernicus, Oscillatoria agardhii, Nostoc paludosum and Rivularia sp. was 97%, 97%, 96% and 91%, respectively. Of the green algae, Chlorella vulgaris var. vulgaris was selected for further experimentation because it had the highest BPA removal and BPA uptake capacity at 87% and 2.84 mg/g dry wt., respectively, and also had the highest growth of the green algae. Hapalosiphon hibernicus was selected because it had the highest BPA removal and BPA uptake capacity at 97% and 3.46 mg/g dry wt., respectively. With initial BPA concentrations at 20, 30 and 40 μM, BPA was rapidly removed within 5 days in both Chlorella vulgaris var. vulgaris (96%, 87% and 87%, respectively) and Hapalosiphon hibernicus (94%, 92% and 89%, respectively). After 5 days, BPA removal was slightly increased in both algae with complete removal by 20 days. At initial BPA concentrations of 40 μM, Chlorella vulgaris vat. vulgaris could remove 8.17 mg/g dry wt. of BPA at day 3 and Hapalosiphon hibernicus could remove 7.97 mg/g dry wt. at the first day. The feasibility of BPA removal by microalgae in leachate was tested at leachate concentrations of 10, 20, 30, 50, 70 and 100%. Hapalosiphon hibernicus died the first day of cultivation in leachate concentrations of 30, 50, 70 and 100%. At a leachate concentration of 20%, Hapalosiphon hibernicus died at day 4 while at a leachate concentration of 10%, it could survive until day 5. At the leachate concentration of 10%, the biomass of Hapalosiphon hibernicus increased and BPA removal ability at day 3 and day 5 were at 46% and 72%, respectively. Hapalosiphon hibernicus had high Bisphenol A removal and utilization of this microalga for the treating of leachate and wastewater containing BPA in Thailand is possible and economical. Copyright © Enviromedia.